THE INFLUENCE OF EDUCATION, EXPERIENCE, AND TRAINING ON AUDIT QUALITY THROUGH PROFESSIONAL COMPETENCE - Ferdianto; A. Nadirah; Muh. Yusuf; Junaidi, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Audit is the process of looking for evidence and evaluating the evidence, which is then outlined in the audit report. An auditor in carrying out an audit must be competent and have a professional attitude in carrying out his duties and responsibilities, to ensure and give confidence that the audit results are reliable and trustworthy. The purpose of this study is to examine the Influence of Education, Experience, and Training on Audit Quality through Professional Competence. The research method with a quantitative approach, using a questionnaire with a Likert scale to search for primary data. The analysis was used with variance-based Structural Equation Modelling (SEM) with the help of SmartPLS application. The results of the study show that: 1) education, experience, and training have a significant effect on professional competence. 2) Education, experience, and training have a significant effect on audit quality. 3) Education, experience, and training have a significant effect on audit quality through professional competence as an intervening variable.